Peran Pemerintah Lokal Dalam Pembangunan Perkotaan di Negara Berkembang - Jhonny Patta (The Institute for Research and Community Services, Institut Teknologi Bandung, 1996)
The relation between local government and urban development is dynamic and interactive. It is influenced by multinational relationship and global issues, but most of the impacts of multinational relationships and global issues are directly related to the role of national government and indirectly to the role of local government. Nevertheless, the role of local government in urban development cannot be simply explained by its position relative to the national government. Instead, it encompasses a complex set of behavior (Daland, ed.1969) and associated with other influences in formulating, deciding, and achieving general and specific goals of urban development. According to Sherwood (1969)